Analysis of Public Transportation (Trans Metro Dewata Bus) as a Congestion Solution - Kariyana, I Made; Sumarda, Gede; Diasa, I Wayan; Pamungkas, Tri Hayatining; Putra, I Putu Esa Mahardika (Universitas Negeri Semarang, 2024)
In urban areas in Indonesia, traffic jams are usually not spared due to the large number of movement activities caused by the community. As happens on Gajah Mada Road, Denpasar, there are pretty frequent traffic jams, considering that this area is located in the middle of the city, where there are shophouses or shops situated side by side almost all the way. This problem is worthy and interesting to research to find out the situation. If passing vehicles are made to ride public transportation, how significant an impact will be, considering that the public transportation (Trans Metro Dewata) that often crosses this road is not operating as intended. The analysis was carried out in 3 time periods, with each period, namely morning at 06.00 - 08.00 WITA, noon at 11.00 - 13.00 WITA, and afternoon at 16.00 - 18.00 WITA. Based on the use of analysis of road performance in the form of degree of saturation with adjusted road service levels, and varied by adding assumptions regarding the use of public transportation that is likely to be effective. So, the results obtained align with the direction of this research, which found that between the original traffic flow conditions and the existing assumptions, there was a change of 7% to 24% in the level of road service. This is quite influential because it can be applied as a solution to the congestion.